PERSEPSI GURU TERHADAP PEMBINAAN KOMPETENSI PROFESIONAL GURU OLEH KEPALA SEKOLAH DI SMP NEGERI 18 PADANG - Sri Silvia (Universitas Negeri Padang, 2013)
The research is aimed to know teachers perception towards coaching the professional competence of teachers by the principal at Junior High School 18 Padang. The Population of this research is all teachers of Junior High School 18 Padang which has total numbers 77 people. Technique sample ofis Stratified Random Sampling, by using Cochran formula. Sample in this research 39 people. The data is analyzed trough average score. The overall research result is that coaching the pofessional competence of teachers by the principal at Junior High School 18 Padang is good enough. Key word: Coaching, Professional Competence of Teachers